Characterization of baked egg custard formulated using suji leaf juice - Herly Evanuarini; Hemas Azizila Nidhal (Postgraduate, University of Mataram, 2025)
The purpose of this study was to find out the physicochemical characteristics of baked egg custard adding 1%, 2%, and 3% of suji leaf juice with a control sample that had no addition. Four treatments and five replications were used in a fully randomized design. Standard laboratory techniques were used to examine the following: texture, pH, yield, color (L, a*, b*), proximate composition, and crude fiber. Data of baked egg custard were processed using ANOVA and Duncan's Multiple Range Test to identify significant differences. The addition of suji leaf juice had a substantial impact on all measured parameters, according to the results (P<0.01). In terms of protein, fat, and crude fiber content, as well as improved texture and color qualities, the custard made with 3% suji leaf juice was highest quality. Improved product stability and sensory appeal were also demonstrated by the pH, yield, and moisture content. According to the results, suji leaf juice optimally improves the physicochemical quality of baked egg custard when added at a rate of 3%. This makes it a promising ingredient for dessert goods that are both functional and aesthetically pleasing.